The spatial integration of potato wholesale markets of Uttarakhand in India - Kumar, A; Mishra, R (SAARC Journal of Agriculture, 2017)
This paper analyzes the spatial integration of potato markets in Uttarakhand using monthly wholesale price for ten years. The maximum likelihood method of cointegration developed by Johansen (1988) was used in the study. The dynamics of short-run price responses were examined using vector error correction model (VECM). The results indicated that five potato markets reacted on the long-run cointegrating equations while the speed of price adjustment in the short-run was almost absent. Moreover, it was found that the longer the distance between the markets, the weaker the integration was. To increase the efficiency of potato markets in Uttarakhand, there is need to focus on building an improved market information system. This system should be able to disseminate timely market information about price, demand and supply of produce to enable producers, traders and consumers to make proper production and marketing decisions. SAARC J. Agri., 14(2): 20-30 (2016)